Identifikasi Pengembangan Daya Tarik Wisata Pada Dusun Kabo Jaya, Desa Swarga Bara, Kecamatan Sangatta Utara, Kabupaten Kutai Timur - Muhammad Fauzan Noor; Justina Ade; Fareis Althalets (Samarinda State Polytechnic, 2019)
The emergence of the concept of ecotourism is one of the alternative travel forms that adopt the principles of sustainable tourism, and tourist activity is more focused on concern for the conservation of nature and culture. Kabo Jaya village next to the Kutai National Park(TNK) has a role as one entry and transit point for travellers. People in the town have a role in preparing some needs of tourists and travellers involved in up to KNP. Warga this village could not capitalize on tourists visiting optimally as potential economic benefits. Citizens who are members of the Travel Awareness Group (Pokdarwis) the need to identify an existing tourist attraction, be it cultural, agro, and natural attractions and the development of programs and activities of the development of the tourist attraction. The method used is the SWOT analysis. Internal review of tourism in the village of Kabo Jaya covering the aspects of strength (strength), weakness (weakness); and external assessment that includes opportunities (opportunity) and threats (threat). Tourist attraction owned by, among others, Fascination Nature (Prefab, Telaga Batu Arang and Tour Susur River), Tourist Attractions Art and Culture, Culinary and souvenirs, Special Interest Travel Attractions (Agro, Plantation, Ranch).